Fa'aaliat Thariqat at-Ta'allum at-Ta'awunii min Naw'i La'bi al-Ijabah 'alaa Nata'iji Ta'lim al-Mufradaat fii as-shaffi al-Tsaani 'Asyarawa fii al-Madrasah al-Tsaanawiyah al-Islamiyah Darul Ulum Samaranj - Wafiq Alya Mustafida; Naifah; Muslam; Hammam; Ach. Fahmi Alwan (Mantiqu Tayr: Journal of Arabic Language, 2024)
Arabic language learning in grades 10 and 12 still uses conventional methods which apparently have an impact on the lack of vocabulary mastery, seen from the arabic language scores that are below average. This is reflected in the arabic exam scores which are below average. The purpose of this study is to encourage student activeness and improve vocabulary learning outcomes. This research uses experimental method by comparing 2 learning models, namely conventional learning model and cooperative learning model. Conventional learning models tend to be passive and focus on lectures. Cooperative learning, on the other hand, involves collaborative and interactive activities. This model proves that conventional learning produces below-average scores, and cooperative learning of answer play type produces higher scores and has a significant positive impact on the mastery of Arabic mufrodat. It is proven from the pretest and posttest results of 7 to 18, this proves that cooperative learning is an effective alternative compared to the conventional method. Further research can explore how the same cooperative learning model can be applied to other language skills, this will help to see if this model is also effective in improving overall Arabic language skills.